High-binding-force and high-conductivity functional aluminum film and preparation method thereof
By adding modified graphene and graphene oxide to the base film layer and coating an aluminum film on its surface, the problems of binding force and conductivity of the functional current collector in the electrolyte environment are solved, thereby improving the safety and life of the battery.
Patent Information
- Application Number
- CN202510874766.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-09-12
AI Technical Summary
The existing functional current collector has poor adhesion between the metal layer and the polymer layer in an electrolyte environment and poor structural stability, resulting in weak bonding and low conductivity, which affects the cycle life and safety of the battery.
Graphene and graphene oxide are added to the base film layer as conductive agents, and their dispersibility in the polymer is improved through modification. At the same time, the surface of the base film layer is covered with the conductive agent and then aluminum film is plated to improve the bonding strength between aluminum and the base film layer by chemical bonds.
The bonding strength and conductivity of the functional aluminum film are improved, the risk of coating peeling is reduced, and the safety and cycle life of the battery are enhanced.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional current collectors, in particular to a functional aluminum film with high bonding strength and high conductivity and a preparation method thereof. Background Art
[0002] In order to achieve the goals of high energy density, lightweight and flexibility for batteries, traditional aluminum foil current collectors can no longer meet the needs. Against this background, a functional current collector with a "sandwich structure" came into being. The middle polymer-based film layer can play a role similar to a fuse when the battery fails, such as a short circuit, to achieve a "short-circuit effect" and significantly improve thermal stability. When the battery is broken by an external impact, almost no metal burrs are generated, which avoids puncturing the battery separator, reduces the risk of battery short circuits, and greatly improves battery safety. In addition, even if the battery causes an internal short circuit due to puncture or other reasons, the short circuit cannot continue due to the fusing effect of the functional current collector. At the same time, compared with the pure metal layer, the functional current collector has better ductility and lower surface density in the polymer-based film, which can increase the energy density of the battery.
[0003] At present, the functional current collector has the problem of poor electrolyte resistance. In the electrolyte environment system, the metal layer and the polymer layer have poor adhesion and poor structural stability, which will cause serious metal delamination, causing the functional current collector to experience a drop in power when used at the battery end, which brings serious problems to the cycle life. At the same time, since the base film layer uses a polymer, this also makes the conductivity of the composite aluminum foil lower than that of traditional aluminum foil. At present, the functional current collector aluminum film and the base film layer are mostly combined by evaporation, and the aluminum and the base film are combined by mechanical interlocking. This makes the bonding between the base layer and the base film weak and cannot be maintained for a long time in the electrolyte environment, resulting in the coating falling off. At the same time, in order to ensure the thickness advantage, the overall conductivity is also slightly lower than that of traditional aluminum foil. Summary of the Invention
[0004] The object of the present invention is to provide a functional aluminum film with high bonding strength and high conductivity and a preparation method thereof, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a functional aluminum film with high bonding strength and high conductivity comprises the following steps: After the polymer raw material is dried and dehydrated, a primary conductive agent is added, and a diaphragm is cast after high-temperature melting. The surface of the diaphragm is covered with a secondary conductive agent. After preheating, longitudinal stretching, transverse stretching and heat setting are carried out in sequence, and air cooling is performed to obtain a base film layer; the base film layer is then cut, thickness measured and corona treated in sequence, and an aluminum film layer is deposited after winding.
[0006] The conductive agent is a mixed powder of graphene and graphene oxide; Preferably, the mass ratio of graphene to graphene oxide in the conductive agent is (1-3):1; Preferably, the amount of the primary conductive agent added is 0.5 wt% of the polymer raw material; Preferably, the amount of the secondary conductive agent added is 0.2 wt % of the polymer raw material; Preferably, the working conditions for high temperature melting are: temperature of 280-300°C, melting heating time of 2-3 minutes; Preferably, the preheating working conditions are: temperature 180-200°C, time 3-5 minutes; Preferably, the working parameters of longitudinal stretching are set as follows: preheating roller temperature is 70-75°C, slow stretching roller temperature is 90-95°C, fast stretching roller temperature is 45-50°C, cooling roller temperature is 25-35°C, and longitudinal stretch ratio is 2-2.5; Preferably, the working parameters of transverse stretching are set as follows: the temperature of the preheating roller is 80-85°C, the temperature of the slow stretching roller is 90-95°C, and the transverse stretching ratio is 2.5-3; Preferably, the working conditions for heat setting are 190-195°C for 3-5 seconds; air cooling to a temperature of 40-45°C; Preferably, the polymer raw material is one or more combinations of polyethylene terephthalate, polyethylene, polypropylene, polyimide, polycarbonate, polyphenylene ether, polyvinyl chloride, polyamide and polytetrafluoroethylene; Preferably, the graphene is modified in the primary conductive agent, specifically comprising the following steps: ultrasonically dispersing the graphene and furoic acid for 1 hour, placing the graphene in N-methylpyrrolidone, reacting at 120-180° C. for 12-14 hours, washing with alcohol water, filtering and drying to obtain a solid, transferring the solid into deionized water and adding hexadecyltrimethylammonium bromide for 1 hour, adding pyrrole and aminosulfonic acid for ultrasonic treatment for 40-50 minutes, and then adding ammonium persulfate for ultrasonic reaction for 10-20 minutes, reacting at 1-5° C. for 24 hours, filtering, washing, and drying to obtain the modified graphene; The mass ratio of graphene to furoic acid is 1:(10-20); the dosage ratio of solid to pyrrole and aminosulfonic acid is 1g:2mL:(0.5-0.9)g; Preferably, the graphene oxide is pretreated in the secondary conductive agent, and the pretreatment steps are: placing the graphene oxide in isopropyl alcohol for ultrasonic dispersion, adding nickel acetate tetrahydrate, heating in a water bath at 80-85°C, stirring for 20-30 minutes, adding deionized water, keeping the temperature for 30 minutes, and then centrifuging and drying, and calcining at 250-300°C for 1-2 hours under an argon atmosphere; wherein the mass ratio of nickel acetate to graphene oxide is (0.6-1.5):1; The working conditions of corona treatment are: power 7kW, winding speed 70m / min, tension at the unwinding end at 60N, tension at the winding end at 60N; After corona treatment, the aluminum film is rolled up and deposited. The aluminum film is deposited by magnetron sputtering and vacuum evaporation or a combination of the two. When winding the deposited aluminum film layer, the tension at the unwinding end is 110N, and the tension at the winding end is 120N; Preferably, the process parameters of vacuum evaporation are: vacuum degree is 5×10 -2 Pa, winding speed is 290-310m / min, evaporation boat heating temperature is 1000-1200℃, wire feeding speed is 300-350mm / min; A functional aluminum film with high bonding strength and high conductivity is obtained by the above preparation method.
[0007] Compared with the prior art, the present invention has the following beneficial effects: 1. The functional aluminum film prepared by the present invention includes a base film layer and an aluminum film layer arranged on the surface of the base film layer. A certain proportion of graphene and graphene oxide are added in the preparation of the base film layer. The addition of graphene (GF) can improve the conductivity to a certain extent. However, due to the structural influence of GF, it is difficult to disperse in the high molecular polymer and easily forms agglomerates, thereby affecting the overall conductive effect. On the contrary, graphene oxide (GO) not only has good dispersibility in the polymer, but also tends to form hydrogen bonds with the polymer. Polymers that are only hydrogen bond acceptors have a lower tendency to form intercalation-type agglomerations, which is conducive to the dispersion of GO. This not only ensures the bonding strength of GO and GF to the base film, but also improves the overall conductivity of the functional aluminum film. In addition, aluminum and GF can form a composite material. Above 600°C, aluminum vapor and graphene combine to form Al4C3, which makes the bonding strength between Al and the base film stronger in the form of chemical bonds; 2. Add a conductive agent to the base film layer of the functional aluminum film, wherein the graphene is modified. First, furoic acid is used to realize GF carboxylation through DA reaction, and then the pyrrole monomer is polymerized on the surface of the carboxylated GF with an oxidant to improve the dispersibility of GF in the polymer. The carboxyl group of the carboxylated graphene will interact with the NH of polypyrrole to produce π-π conjugation, thereby improving the conductivity. At the same time, aminosulfonic acid is doped with polypyrrole to introduce sulfonate groups to further improve the conductivity. When the surface of the base film layer is covered with a conductive agent and then aluminum film is plated, GO is heated and calcined with nickel acetate to obtain a mixed material of graphene oxide and nickel oxide. The intervention of nickel oxide optimizes the interface bonding between graphene and aluminum, improves the bonding strength between the base film layer and the aluminum film layer, and reduces the risk of coating shedding. DETAILED DESCRIPTION
[0008] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0009] In the experiment, graphene was purchased from Sinopharm Group with the Sinopharm code XW011034343980012; Graphene oxide was purchased from Titan Technology's self-search platform. It is a graphene oxide aqueous dispersion with the model number GO-2 and an average particle size of 0.05 μm. It was dried at 80°C before use. The polymer raw material is polyethylene terephthalate, which is obtained by mixing dimethyl terephthalate and ethylene glycol in a molar ratio of 1:1.5, adding 0.01wt% antimony acetate, and stirring at 200°C for 4 hours. Dimethyl terephthalate is purchased from the self-exploration platform of Titan Technology. It is a powdered solid with a purity of 99%, RG grade, and product number 01012938. Ethylene glycol is purchased from the self-exploration platform of Titan Technology. It is a barreled liquid with a purity of ≥99.5% and product number 013446056. Example 1: This example provides a method for preparing a functional aluminum film with high bonding strength and high conductivity. The specific steps are as follows: The polymer raw material was taken, dried and dehydrated, and then hot-melted. A primary conductive agent was added, melted and heated at 300°C for 2 minutes, and then transferred to a mold. A secondary conductive agent was added and covered on the surface of the molten polymer. After heating at 200°C for 5 minutes, longitudinal stretching and transverse stretching were performed in sequence, and then heat-setting was performed. After standing at 195°C for 5 seconds, it was air-cooled to 45°C to obtain a base film layer. Then, it was cut and measured to obtain a 6μm base film layer, in which the secondary conductive agent coverage thickness was 0.1μm; then, it was corona treated and wound at 7kW power, 70m / min winding speed, 60N tension at the unwinding end, and 60N tension at the winding end. Then, with the tension of the unwinding end being 110N and the tension of the winding end being 120N, the winding trolley was pulled into the evaporation chamber to deposit a 1μm aluminum film layer, and vacuumed to 5×10 -2 Pa, the winding trolley is turned on and the speed is controlled to 300m / min, the evaporation boat is heated to 1200℃, and the wire feeding speed is 320mm / min to obtain a functional aluminum film; The working parameters of longitudinal stretching are as follows: preheating roller temperature is 75°C, slow stretching roller temperature is 95°C, fast stretching roller temperature is 45°C, cooling roller temperature is 25°C, and longitudinal stretching ratio is 2.5 times; The working parameters of transverse stretching were set as follows: preheating roller temperature of 85°C, slow stretching roller temperature of 95°C, and transverse stretching ratio of 3 times; The conductive agent includes graphene and graphene oxide in a mass ratio of 1:1; The amount of primary conductive agent added is 0.5wt% of the polymer raw material; The amount of the secondary conductive agent added is 0.2 wt% of the polymer raw material.
[0010] Example 2: Referring to Example 1, the mass ratio of graphene and graphene oxide in the conductive agent was adjusted to 1.5:1. The specific steps are as follows: The polymer raw material was taken, dried and dehydrated, and then hot-melted. A primary conductive agent was added, melted and heated at 300°C for 2 minutes, and then transferred to a mold. A secondary conductive agent was added and covered on the surface of the molten polymer. After heating at 200°C for 5 minutes, longitudinal stretching and transverse stretching were performed in sequence, and then heat-setting was performed. After standing at 195°C for 5 seconds, it was air-cooled to 45°C to obtain a base film layer. Then, it was cut and measured to obtain a 6μm base film layer, in which the secondary conductive agent coverage thickness was 0.1μm; then, it was corona treated and wound at 7kW power, 70m / min winding speed, 60N tension at the unwinding end, and 60N tension at the winding end. Then, with the tension of the unwinding end being 110N and the tension of the winding end being 120N, the winding trolley was pulled into the evaporation chamber to deposit a 1μm aluminum film layer, and vacuumed to 5×10 -2 Pa, the winding trolley is turned on and the speed is controlled to 300m / min, the evaporation boat is heated to 1200℃, and the wire feeding speed is 320mm / min to obtain a functional aluminum film; The working parameters of longitudinal stretching are as follows: preheating roller temperature is 75°C, slow stretching roller temperature is 95°C, fast stretching roller temperature is 45°C, cooling roller temperature is 25°C, and longitudinal stretching ratio is 2.5 times; The working parameters of transverse stretching were set as follows: preheating roller temperature of 85°C, slow stretching roller temperature of 95°C, and transverse stretching ratio of 3 times; The conductive agent includes graphene and graphene oxide in a mass ratio of 1.5:1; The amount of primary conductive agent added is 0.5wt% of the polymer raw material; The amount of the secondary conductive agent added is 0.2 wt% of the polymer raw material.
[0011] Example 3: Referring to Example 1, the mass ratio of graphene and graphene oxide in the conductive agent was adjusted to 2:1. The specific steps are as follows: The polymer raw material was taken, dried and dehydrated, and then hot-melted. A primary conductive agent was added, melted and heated at 300°C for 2 minutes, and then transferred to a mold. A secondary conductive agent was added and covered on the surface of the molten polymer. After heating at 200°C for 5 minutes, longitudinal stretching and transverse stretching were performed in sequence, and then heat-setting was performed. After standing at 195°C for 5 seconds, it was air-cooled to 45°C to obtain a base film layer, which was then cut and measured to obtain a 6μm base film layer, in which the secondary conductive agent coverage thickness was 0.1μm; then the film was corona treated and wound at 7kW power, 70m / min winding speed, 60N tension at the unwinding end, and 60N tension at the winding end. Then, the film-unwinding end tension was 110N and the winding end tension was 120N, and the winding trolley was pulled into the evaporation chamber to deposit a 1μm aluminum film layer, and vacuumed to 5×10 -2 Pa, the winding trolley is turned on and the speed is controlled to 300m / min, the evaporation boat is heated to 1200℃, and the wire feeding speed is 320mm / min to obtain a functional aluminum film; The working parameters of longitudinal stretching are as follows: preheating roller temperature is 75°C, slow stretching roller temperature is 95°C, fast stretching roller temperature is 45°C, cooling roller temperature is 25°C, and longitudinal stretching ratio is 2.5 times; The working parameters of transverse stretching were set as follows: preheating roller temperature of 85°C, slow stretching roller temperature of 95°C, and transverse stretching ratio of 3 times; The conductive agent includes graphene and graphene oxide in a mass ratio of 2:1; The amount of primary conductive agent added is 0.5wt% of the polymer raw material; The amount of the secondary conductive agent added is 0.2 wt% of the polymer raw material.
[0012] Example 4: Referring to Example 1, the mass ratio of graphene and graphene oxide in the conductive agent was adjusted to 2.5:1. The specific steps are as follows: The polymer raw material was taken, dried and dehydrated, and then hot-melted. A primary conductive agent was added, melted and heated at 300°C for 2 minutes, and then transferred to a mold. A secondary conductive agent was added and covered on the surface of the molten polymer. After heating at 200°C for 5 minutes, longitudinal stretching and transverse stretching were performed in sequence, and then heat-setting was performed. After standing at 195°C for 5 seconds, it was air-cooled to 45°C to obtain a base film layer, which was then cut and measured to obtain a 6μm base film layer, in which the secondary conductive agent coverage thickness was 0.1μm; then 7kW power, 70m / min winding speed, 60N tension at the unwinding end and 60N tension at the winding end for corona treatment and winding, and then with the tension of the unwinding end being 110N and the tension of the winding end being 120N, the winding trolley was pulled into the evaporation chamber to deposit a 1μm aluminum film layer, and vacuumed to 5×10 -2 Pa, the winding trolley is turned on and the speed is controlled to 300m / min, the evaporation boat is heated to 1200℃, and the wire feeding speed is 320mm / min to obtain a functional aluminum film; The working parameters of longitudinal stretching are as follows: preheating roller temperature is 75°C, slow stretching roller temperature is 95°C, fast stretching roller temperature is 45°C, cooling roller temperature is 25°C, and longitudinal stretching ratio is 2.5 times; The working parameters of transverse stretching were set as follows: preheating roller temperature of 85°C, slow stretching roller temperature of 95°C, and transverse stretching ratio of 3 times; The conductive agent includes graphene and graphene oxide in a mass ratio of 2.5:1; The amount of primary conductive agent added is 0.5wt% of the polymer raw material; The amount of the secondary conductive agent added is 0.2 wt% of the polymer raw material.
[0013] Example 5: Referring to Example 1, the mass ratio of graphene and graphene oxide in the conductive agent was adjusted to 3:1. The specific steps are as follows: The polymer raw material was taken, dried and dehydrated, and then hot-melted. A primary conductive agent was added, melted and heated at 300°C for 2 minutes, and then transferred to a mold. A secondary conductive agent was added and covered on the surface of the molten polymer. After heating at 200°C for 5 minutes, longitudinal stretching and transverse stretching were performed in sequence, and then heat-setting was performed. After standing at 195°C for 5 seconds, it was air-cooled to 45°C to obtain a base film layer, which was then cut and measured to obtain a 6μm base film layer, in which the secondary conductive agent coverage thickness was 0.1μm; then 7kW power, 70m / min winding speed, 60N tension at the unwinding end and 60N tension at the winding end for corona treatment and winding, and then with the tension of the unwinding end being 110N and the tension of the winding end being 120N, the winding trolley was pulled into the evaporation chamber to deposit a 1μm aluminum film layer, and vacuumed to 5×10 -2 Pa, the winding trolley is turned on and the speed is controlled to 300m / min, the evaporation boat is heated to 1200℃, and the wire feeding speed is 320mm / min to obtain a functional aluminum film; The working parameters of longitudinal stretching are as follows: preheating roller temperature is 75°C, slow stretching roller temperature is 95°C, fast stretching roller temperature is 45°C, cooling roller temperature is 25°C, and longitudinal stretching ratio is 2.5 times; The working parameters of transverse stretching were set as follows: preheating roller temperature of 85°C, slow stretching roller temperature of 95°C, and transverse stretching ratio of 3 times; The conductive agent includes graphene and graphene oxide in a mass ratio of 3:1; The amount of primary conductive agent added is 0.5wt% of the polymer raw material; The amount of the secondary conductive agent added is 0.2 wt% of the polymer raw material.
[0014] Example 6: Referring to Example 2, the graphene in the primary conductive agent is modified and the graphene oxide in the secondary conductive agent is pretreated. The specific steps are as follows: The polymer raw material was taken, dried and dehydrated, and then hot-melted. A primary conductive agent was added, melted and heated at 300°C for 2 minutes, and then transferred to a mold. A secondary conductive agent was added and covered on the surface of the molten polymer. After heating at 200°C for 5 minutes, longitudinal stretching and transverse stretching were performed in sequence, and then heat-setting was performed. After standing at 195°C for 5 seconds, it was air-cooled to 45°C to obtain a base film layer, which was then cut and measured to obtain a 6μm base film layer, in which the secondary conductive agent coverage thickness was 0.1μm; then the film was corona treated and wound at 7kW power, 70m / min winding speed, 60N tension at the unwinding end, and 60N tension at the winding end. Then, the film-unwinding end tension was 110N and the winding end tension was 120N, and the winding trolley was pulled into the evaporation chamber to deposit a 1μm aluminum film layer, and vacuumed to 5×10 -2 Pa, the winding trolley is turned on and the speed is controlled to 300m / min, the evaporation boat is heated to 1200℃, and the wire feeding speed is 320mm / min to obtain a functional aluminum film; The working parameters of longitudinal stretching are as follows: preheating roller temperature is 75°C, slow stretching roller temperature is 95°C, fast stretching roller temperature is 45°C, cooling roller temperature is 25°C, and longitudinal stretching ratio is 2.5 times; The working parameters of transverse stretching were set as follows: preheating roller temperature of 85°C, slow stretching roller temperature of 95°C, and transverse stretching ratio of 3 times; The primary conductive agent includes modified graphene and graphene oxide in a mass ratio of 1.5:1; The secondary conductive agent includes graphene and pretreated graphene oxide in a mass ratio of 1.5:1; The amount of primary conductive agent added is 0.5wt% of the polymer raw material; The amount of secondary conductive agent added is 0.2wt% of the polymer raw material; The modified graphene was prepared by ultrasonically dispersing 1 g of graphene and 15 g of furoic acid for 1 hour, placing the mixture in 100 mL of N-methylpyrrolidone, reacting the mixture at 180° C. for 12 hours, washing the mixture with alcohol water, and then filtering and drying the mixture to obtain a solid. 1 g of the solid was transferred to 200 mL of deionized water, and 1 g of hexadecyltrimethylammonium bromide was added and ultrasonically dispersed for 1 hour. 2 mL of pyrrole and 0.8 g of aminosulfonic acid were added and ultrasonically treated for 40 minutes, followed by adding 1 g of ammonium persulfate and ultrasonically reacting for 20 minutes. The mixture was reacted at 1° C. for 24 hours, filtered, washed, and dried to obtain the modified graphene. The preparation method of pretreated graphene oxide is as follows: 1 g of graphene oxide is placed in 100 mL of isopropanol and ultrasonically dispersed, 0.66 g of nickel acetate tetrahydrate is added and heated in a water bath at 85°C, stirred for 30 minutes, 10 mL of deionized water is added and kept warm for 30 minutes, and then centrifuged and dried, and calcined at 250°C for 1 hour under an argon atmosphere.
[0015] Comparative Example: As a control experiment of Examples 1-6, no conductive agent was added, and aluminum oxide was added as a base layer. The specific steps are as follows: The polymer raw material was dried and dehydrated, and then hot-melted. After melting and heating at 300 ° C for 2 minutes, it was transferred to the mold, heated at 200 ° C for 5 minutes, and then longitudinally stretched and transversely stretched in sequence, and then heat-set. After standing at 195 ° C for 5 seconds, it was air-cooled to 45 ° C, and then slit and measured to obtain a 6 μm base film. The film was corona treated and wound at a power of 7 kW, a winding speed of 70 m / min, a tension of 60 N at the unwinding end, and a tension of 60 N at the winding end. The film was then pulled into the evaporation chamber with a tension of 110 N at the unwinding end and a tension of 120 N at the winding end, and vacuumed to 5×10 -3 Pa, start the winding trolley, control the speed at 300m / min, the evaporation boat temperature is 1200℃, start the oxygen, start the wire feeding, and the wire feeding speed is 100mm / min. After the 3nm base layer is plated, the vacuum is broken, and the winding trolley enters the evaporation chamber again and the vacuum is pumped to 5×10 -2 Pa, the winding trolley is turned on and the speed is controlled to 300m / min, the evaporation boat is heated to 1200℃, the wire feeding speed is 320mm / min, and a 1μm aluminum layer is deposited to obtain an aluminum film; The working parameters of longitudinal stretching are as follows: preheating roller temperature is 75°C, slow stretching roller temperature is 95°C, fast stretching roller temperature is 45°C, cooling roller temperature is 25°C, and longitudinal stretching ratio is 2.5 times; The working parameters of transverse stretching are set as follows: preheating roller temperature is 85℃, slow stretching roller temperature is 95℃, and transverse stretching ratio is 3 times.
[0016] Detection test Sheet resistance test: A four-probe resistivity tester was used to test the aluminum films prepared in Examples 1-6 and the comparative example at five points along the MD direction, one point every 100 nm. The test was conducted at 20°C in accordance with GB / T 22638.6-2016. The data are recorded in Table 1. Peel force test: The finished aluminum films prepared in Examples 1-6 and the comparative example were cut into 6×8 cm specifications and packaged with aluminum-plastic film. Two finished aluminum films were placed in each bag. 10 mL of ternary electrolyte (solute: 1 M LiPF6, solvent: EC, DMC, and EMC blended in a mass ratio of 3:3:4) was injected into each bag of samples in a glove box and packaged. After being placed for different days (1 / 3 / 7 / 15 / 30), the samples were taken out and soaked in ethanol in a fume hood to clean the surface electrolyte. One side of the 3M-9080A-15mm tape was attached to a stainless steel plate, and the other side was bonded to samples that had been placed for different days (1 / 3 / 7 / 15 / 30). The tape was squeezed back and forth twice with a 2 kg standard small pressure roller, and then placed on a tensile testing machine to stretch 180° at a speed of 100 mm / min. The peel force was measured, and the maximum value was taken. The data is recorded in Table 2.
[0017] Table 1 Surface resistance of the examples and comparative examples at different elongation points
[0018] Table 2 Peel force data of functional aluminum films prepared in Examples and Comparative Examples
[0019] Conclusion: It can be seen from Table 1 and Table 2 that the conductivity can be improved by introducing GF into the base film in the present invention. It can be seen from Examples 1-5 in Table 1 that the more the amount added, the better the effect. However, the relatively poor dispersion will lead to uneven sheet resistance. Therefore, when the mass ratio of GF to GO is 1.5:1 (the volume ratio is close at this time), the effect is the best and the conductivity is the best. Example 6 improves the dispersion of GF, the sheet resistance is more uniform, and the conductivity is improved compared with Example 1. GO not only has good dispersion in the polymer, but also tends to form hydrogen bonds with the polymer, thereby not only maintaining The bonding strength of GO and GF to the base film is confirmed while ensuring electrical conductivity. As shown in Table 2 Examples 1-6 and Comparative Examples, the electrolyte resistance and peeling strength are greatly improved after the addition of GO and GF, and when the volume ratio of GF and GO is close, the dispersion effect is the best, thereby making the membrane surface bonding more uniform. Therefore, Example 3 has the best effect. The modification and pretreatment of Example 6 effectively improve the bonding strength between Al and the base film layer, achieving better anti-stripping effect than Example 1. Aluminum and GF can form a composite material to form Al4C3, which makes the bonding strength between Al and the base film stronger in the form of chemical bonds.
[0020] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations that come within the meaning and range of equivalents of the claims be embraced therein.
Claims
1. A method for preparing a functional aluminum film with high bonding strength and high conductivity, characterized in that: The preparation method includes the following steps: drying and removing water from the polymer raw material, adding a primary conductive agent, melting at high temperature and casting a membrane, covering the surface of the membrane with a secondary conductive agent, preheating and sequentially performing longitudinal stretching, transverse stretching and heat setting, and air cooling to obtain a base membrane layer; then the base membrane layer is sequentially cut, thickness measured and corona treated, and an aluminum film layer is deposited after winding.
2. The method for preparing a functional aluminum film with high bonding strength and high conductivity according to claim 1, characterized in that: The conductive agent is a mixed powder of graphene and graphene oxide; the mass ratio of graphene to graphene oxide is (1-3):1; the addition amount of the primary conductive agent is 0.5wt% of the polymer raw material; and the addition amount of the secondary conductive agent is 0.2wt% of the polymer raw material.
3. The method for preparing a functional aluminum film with high bonding strength and high conductivity according to claim 1, characterized in that: The working conditions for high-temperature melting are: temperature of 280-300℃, time of 2-3min; the working conditions for preheating are: temperature of 180-200℃, time of 3-5min; the working parameters for longitudinal stretching are set as: preheating roller temperature of 70-75℃, slow pulling roller temperature of 90-95℃, fast pulling roller temperature of 45-50℃, cooling roller temperature of 25-35℃, and longitudinal stretch ratio of 2-2.5; the working parameters for transverse stretching are set as: preheating roller temperature of 80-85℃, slow pulling roller temperature of 90-95℃, and transverse stretch ratio of 2.5-3; the working conditions for heat setting are: temperature of 190-195℃, time of 3-5s; and air cooling to a temperature of 40-45℃.
4. The method for preparing a functional aluminum film with high bonding strength and high conductivity according to claim 1, characterized in that: The polymer raw material is one or more combinations of polyethylene terephthalate, polyethylene, polypropylene, polyimide, polycarbonate, polyphenylene ether, polyvinyl chloride, polyamide and polytetrafluoroethylene.
5. The method for preparing a functional aluminum film with high bonding strength and high conductivity according to claim 1, characterized in that: Graphene is modified in a primary conductive agent, and the specific steps are as follows: graphene and furoic acid are ultrasonically dispersed for 1 hour, then placed in N-methylpyrrolidone, reacted at 120-180°C for 12-14 hours, washed with alcohol water, filtered and dried to obtain a solid, transferred to deionized water and added with hexadecyltrimethylammonium bromide for ultrasonic dispersion for 1 hour, pyrrole and aminosulfonic acid are added for ultrasonic treatment for 40-50 minutes, and then ammonium persulfate is added for ultrasonic reaction for 10-20 minutes, reacted at 1-5°C for 24 hours, filtered, washed, and dried to obtain modified graphene.
6. The method for preparing a functional aluminum film with high bonding strength and high conductivity according to claim 5, characterized in that: The mass ratio of graphene to furoic acid is 1:(10-20); the dosage ratio of solid to pyrrole and aminosulfonic acid is 1g:2mL:(0.5-0.9)g.
7. The method for preparing a functional aluminum film with high bonding strength and high conductivity according to claim 1, characterized in that: Graphene oxide is pretreated in a secondary conductive agent. The pretreatment steps are as follows: ultrasonically disperse the graphene oxide in isopropanol, add nickel acetate tetrahydrate, heat in a water bath at 80-85°C, stir for 20-30 minutes, add deionized water, keep warm for 30 minutes, and then centrifuge and dry. The graphene oxide is calcined at 250-300°C for 1-2 hours under an argon atmosphere. The mass ratio of nickel acetate to graphene oxide is (0.6-1.5):
1.
8. The method for preparing a functional aluminum film with high bonding strength and high conductivity according to claim 1, characterized in that: The working conditions of the corona treatment are: power of 7 kW, winding speed of 70 m / min, tension at the unwinding end of 60 N, and tension at the winding end of 60 N; after the corona treatment, the aluminum film layer is deposited by winding, and the aluminum film layer is deposited by one or a combination of magnetron sputtering and vacuum evaporation.
9. The method for preparing a functional aluminum film with high bonding strength and high conductivity according to claim 8, characterized in that: When the aluminum film is rolled up, the tension at the unwinding end is 110N, and the tension at the winding end is 120N. The process parameters of vacuum evaporation are: vacuum degree 5×10 -2 Pa, the winding trolley speed is 290-310m / min, the evaporation boat heating temperature is 1000-1200℃, and the wire feeding speed is 300-350mm / min.
10. A functional aluminum film with high bonding strength and high conductivity, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.